3-D polymeric structure formed by hydrogen bonds of copper (II) complex. (2nd January 2017) - Gungor, Elif
ABSTRACT: A new copper complex trans -Dichlorobis[4-methoxypyridine]copper(II) (1 ) was synthesized and its crystal structure determined by X-ray diffraction. The close Cu···Cl contacts between the molecular units form bi-bridged dimers. The Copper(II) ion completes its 4 + 2 coordination via interaction with the Cu···Cl close contact. The complex has a polymeric structure of infinite one-dimensional (1D) bi-bridged chains, consisting of six-coordinate copper(II) units. C–H···C l intermolecular interaction connect the 1D-chains in the structure of1 which form to 3D structure. The π ··· π interactions between the aromatic rings are also observed in the hydrogen bonded assembly of1 .